Reimagining Ghana’s cities: Perspectives from the Bible and African Indigenous Sacred Texts - Michael K. Mensah (Theologia Viatorum)
Africa has some of the world’s fastest-growing cities. While urbanisation could be a sign of economic growth, the expansion of these cities is often done at the expense of social and environmental concerns. This article uses the Sacred Texts Approach of African Biblical Hermeneutics in studying Psalm 46. It argues that the two-fold threats to the City of God, namely the cosmic and the human, are the same threats to the cities in Ghana.